(7c-6)(7c+1)
2006-12-27 10:38:22
·
answer #1
·
answered by etihad 3
·
0⤊
0⤋
49c^2 - 35c - 6
To solve this one, you have to use trial and error, for factors of -6.
49c^2 splits up into 7c and 7c, so we'll at least have:
(7c + ?) (7c + ?)
Test factors of -6.
Test -1 and 6:
(7c - 1) (7c + 6). The outside plus inside is equal to 35. However, we want MINUS 35. Whenever we test values and the sign is wrong, all we have to do is switch the sign of both factors. The -1 becomes a +1, and the 6 becomes a -6
(7c + 1) (7c - 6). The outside plus inside is -42 + 7 = -35, which is therefore correct.
2006-12-26 18:45:04
·
answer #2
·
answered by Puggy 7
·
1⤊
0⤋
Looks tough, but notice that 49c^2 is what you get by squaring 7c, and the middle term is -5 multiplied by 7c. So you could use x to represent 7c and write this expression as
x^2 - 5x - 6
We want two numbers which multiply to give -6 and add to give -5. They have to have opposite signs (to give the negative product, i.e. -6) and so 3 and 2 are no good because with opposite signs they add to 1 (or -1). Use -6 and +1:
(x - 6)(x + 1) which of course is (using x = 7c)
(7c - 6)(7c + 1)
2006-12-26 18:47:21
·
answer #3
·
answered by Hy 7
·
1⤊
0⤋
49c^2 - 35c - 6 = (7c - 6)(7c + 1). Looking at 49c^2, it's your best guess that you have 7c*7c, although it could also be 49c*c. Assuming the first, though, you have (7c + a)(7c + b) = 49c^2 - 35c - 6. So you need 7ac + 7bc = -35c, or 7a + 7b = -35, thus a + b = -5. Meanwhile, you also need ab = -6. You need numbers with a product of -6 and a sum of -5. Note that (-6)*1 = -6 and -6 + 1 = -5, so that's your answer. You can take them in either order since both factors were (7c + _), so say a = -6 and b = 1, then (7c + a)(7c + b) = (7c - 6)(7c + 1) = 49c^2 - 35c - 6.
2006-12-26 18:44:42
·
answer #4
·
answered by DavidK93 7
·
0⤊
1⤋
(7c-6)(7c+1)
2006-12-26 18:43:44
·
answer #5
·
answered by 7
·
1⤊
0⤋